The Principle of Continuity as a Subject of Auditor’s Attention: the Strategic Aspect of Planning - Selishchev, S. V. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2018)
The paper investigates and systematizes strategic planning aspects of the validation of the principle of continuity in preparing financial statements management. The research and further development of methodological approaches to the estimation of the principle of continuity in the planning of the audit is carried out. Particular attention is paid to the events and factors that may result in the termination of the business entity’s activities. Analysis of current practice and methodological framework shows that there has not been single methodological model by now, which would ensure development of effective methodological approaches to audit planning, in terms of assessing the impact of these events and risk factors on the termination of activities. Studies of audit planning are in focus of domestic and foreign scientists, but the assessment of the application of the principle of continuity in planning as a key phase of audit needs further consideration and practical adaptation to the existing practice. The purpose of this article is to study and further develop methodological approaches to assessing the principle of continuity when planning an audit. Summarizing the above concepts of audit planning strategies, it should be noted that one of the characteristics of the audit of business continuity are large amounts of information and great many issues that should be investigated separately or together, in order to have the adequately assessed correct application of continuity assessment of business entity by management personnel, which does not allow for continuous verification methods and requires assessment conclusion relying on the auditor’s judgment. Describing the current practice, it should be noted that the planning of audit procedures is performed throughout the audit period as audit plans and the program of audit procedures are developed. For example, planning of audit procedures for risk assessment is usually carried out at the initial stage of the audit. In addition, the auditor may begin performing procedures for some classes of transactions, account balances and complete disclosure till the completion of the more detailed audit plan for the remaining audit procedures.